Difficult question.please solve.
Attachments:
![](https://hi-static.z-dn.net/files/da9/6d2a0c86810979c4e753cb15b1136b35.jpg)
Answers
Answered by
1
take square both sides
(ax+by)^2 = xy
ax^2+by^2+2axby = xy
now 2axby is constant so we can neglect it
hence prove
(ax+by)^2 = xy
ax^2+by^2+2axby = xy
now 2axby is constant so we can neglect it
hence prove
Answered by
0
Answer:
Step-by-step explanation:
take square both sides
(ax+by)^2 = xy
ax^2+by^2+2axby = xy
now 2axby is constant so we can neglect it
hence prove
Similar questions